Research progress on the effects of pregnancy-related risk factors for atopic dermatitis in the offspring - Yuntong WANG; Xiaowu LIU; Yanchun WANG; Fangyi JING; Qiao LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
In recent years, the prevalence of atopic dermatitis in infants and young children has been on the rise. Studies have shown that pregnant women are often affected by environment, diet and other factors during pregnancy and complicated with various diseases. The pregnancy-related risk factors can affect the fetus through the placenta, causing Th1/Th2 imbalance and intestinal flora disorder in newborn, thereby affecting the development of atopic dermatitis in offspring. This article reviews the progress of research on the effects of risk factors, including environmental factors, dietary factors, psychological factors, mode of delivery, and allergies during pregnancy, on atopic dermatitis in the offspring, in order to provide guidance to pregnant women and to reduce the risk of diseases in the offspring.